2020
DOI: 10.1017/cjn.2020.97
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Subtle Cognitive Impairment in Multiple Sclerosis with the Montreal Cognitive Assessment

Abstract: Background: Although cognitive deficits are frequent in multiple sclerosis (MS), screening for them with tools such as the Montreal Cognitive Assessment (MoCA) test is usually not performed unless there is a subjective complaint. The Multiple Sclerosis Neuropsychological Questionnaire (MSNQ) is among the instruments most commonly used to assess self-reported subjective complaints in MS. Nonetheless, it does not always accurately reflect cognitive status; many patients with cognitive deficits thus fail to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Some studies addressed multisystem involvement, such as multiple sclerosis and systemic lupus erythematosus. In addition, studies aiming to see the mental integrity of individuals with chronic diseases such as heart failure and diabetes have also evaluated cognitive functions [10][11][12][13][14][15] . In iron deficiency anemia, oxygen capacity decreases, resulting from both anemia and the decrease of iron in the body.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies addressed multisystem involvement, such as multiple sclerosis and systemic lupus erythematosus. In addition, studies aiming to see the mental integrity of individuals with chronic diseases such as heart failure and diabetes have also evaluated cognitive functions [10][11][12][13][14][15] . In iron deficiency anemia, oxygen capacity decreases, resulting from both anemia and the decrease of iron in the body.…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between GSH levels and cognitive function, using the Montreal Cognitive Assessment (MoCA), was interrogated by half (2/4) the MRS studies, and no significant association was found in the ROIs investigated, namely medial frontal ( Hupfeld et al, 2021 ), sensorimotor ( Hupfeld et al, 2021 ) and occipital ( Emir et al, 2011 ). However, it should be noted that while MoCA can robustly detect mild cognitive impairment, detection of subtle cognitive impairments requires analyses of its sub-scores ( Charest et al, 2020 ), which were not conducted by the above-mentioned studies. In addition to cognition, one study assessed the relationship between GSH levels and mobility in the sensorimotor and frontal cortices ( Hupfeld et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The high reliability of the MoCA in MS patients has been demonstrated by several studies. The test has shown compatible psychometric properties with conventional, more extensive neuropsychological tests used in MS patients—the Brief Repeatable Battery (BRB) and the Minimal Assessment of Cognitive Function in Multiple Sclerosis (MACFIMS) [ 28 , 29 ]. We found a good correlation between BICAMS and MoCA results and feel that the simultaneous application of these instruments increases their diagnostic capacity.…”
Section: Discussionmentioning
confidence: 99%
“…The test evaluates cognitive domains commonly affected in MS patients, such as executive function, visuospatial ability, attention/concentration, verbal fluency, and memory. It has demonstrated efficacy in evaluating cognitive dysfunction accompanying several chronic neurological disorders, including MS [ 28 , 29 ]. Finally, the patients' mental health was evaluated using the Beck Depression Inventory (BDI) [ 30 ].…”
Section: Methodsmentioning
confidence: 99%